Voids to Cementitious Materials Ratio as a Control for Tensile Strength on CTRB with Natural Pozzolan - Joice Elfrida Waani (Jurnal Teknik Sipil, 2022)
Abstrak Posolan alam diklasifikasikan sebagai material tambahan pada campuran Semen (SCMs) karena sifat sementasinya yang jika ditambahkan dalam campuran beton dan semen sebagai bahan aditif berpengaruh positif terhadap campuran. Penelitian ini bertujuan untuk mengetahui pengaruh jumlah posolan alam, tras sebagai substitusi parsial semen Portland, terhadap rasio antara porositas dan kadar material semen pada Indirect Tensile Strength (ITS) dan Resilient Modulus (MR) campuran CTRB. Campuran CTRB yang menjadi target pengujian ini mengandung komposisi Material Reclaimed Asphalt Pavement (RAP) dan Reclaimed Aggregate Materials (RAM) yang berbeda yaitu 40% RAP : 60% RAM dan 60% RAP : 40% RAM. Hasil penelitian menunjukkan bahwa dengan meningkatnya kandungan material semen (Civ*), nilai ITS meningkat seiring dengan penurunan porositas (η) untuk campuran 40% RAP dan 60% RAP CTRB dengan substitusi pozzolan alam 15% dan 30% terhadap kandungan semen 2%, 4% dan 6%. Dalam penelitian ini juga dilakukan pengujian MR terhadap kedua campuran CTRB yang sama dengan variasi derajat tekanan confining dan deviatoric pada 5000 MPa hingga 7900 MPa. Kata-kata Kunci: CTRB, Posolan alam, material tambahan semen, porositas, MR, ITS. Abstract Natural pozzolan is classified as Supplemental Cementitious Materials (SCMs) as it exhibits cementitious properties which is gradually being applied in cement mixtures as additives. This research aims at exploring the effect of trass as natural pozzolan, to the porosity and cementitious ratio on Indirect Tensile Strength (ITS) and Resilient Modulus (MR) in Cement Treated Recycled Base (CTRB) pavement mixtures. CTRB mixtures containing two different proportions of Reclaimed Asphalt Pavement (RAP) and Reclaimed Aggregate Materials (RAM). Mixtures of 40% RAP : 60% RAM and 60% RAP : 40% RAM were considered as target mixtures that can be achieved in the field based on mixture properties related to ITS and MR.  The laboratory investigation confirmed that with increasing of cementitious materials content (Civ*), the ITS value increases in conjunction with the decrease in porosity (η) for the 40% RAP and 60% RAP CTRB mixtures with 15% and 30% natural pozzolan substitution to the 2%, 4% and 6% cement content. In this study, MR tests were also carried out on both mixtures of the same CTRB with variations in the degree of pressure of confining and deviatoric stress at MR test from 5000 MPa to 7900 MPa.. Keywords: CTRB, natural pozzolan, supplemental cementitious materials, porosity, MR, ITS.